Investigation of Life Satisfaction and Work Stress in Employees Doing Office Exercise - Bastug, Gulsum (Progress in Nutrition, 2021)
Study Objectives: This study aims to examine the life satisfaction and work stress level of employees who do and do not do office exercises. Methods: A total of 97 office workers including the experimental (n: 40) and the control group (n: 57) participated in the study. Participants implementing a diet program were not included in the study. Working at Mugla Sıtkı Koçman University with an average age of 41,61 ± 9,46. 15-20 minutes of the office exercise program was applied to the experimental group 3 days a week “The Satisfaction with Life Scale (SWLS)” and “Job Stress Scale” were used to determine the work stress level of office workers. The normality of the data was tested with the Kolmogorov Smirnov Test before the analyses. The Independent samples t-test was performed for normal distributed data. Results: As a result, a significant difference was found between life satisfaction and work stress pretest-posttest values of the employees doing office exercise. The level of work stress in the employees performing office exercise decreases. Work stress was lower in female employees than in male employees. Correlation was determined between office workers' life satisfaction and work stress scores. Conclusion: As the satisfaction of office workers increased work stress decreased.